Study of the protein cargo of extracellular vesicles released by Acute Myeloid Leukemia cell lines - Soure, Inês Adriana Miranda (2024)
Extracellular vesicles (EVs) are nanosized particles that are secreted by almost all cell types within the body. EVs carry complex molecular cargos, such as proteins, nucleic acids and lipids, which can be delivered to recipient cells, thus mediating intercellular signaling and communication between cells. Importantly, the cargo of EVs derives from their cells of origin. Evidence from several studies highlights the role of tumor-derived EVs in promoting tumorigenesis, as well as contributing to drug resistance in both solid tumors and hematological malignancies. Moreover, EVs have gained great prominence as a novel source of biomarkers in liquid biopsies. Acute myeloid leukemia (AML) is a life-threatening disorder of the blood and bone marrow, that progresses rapidly. EVs have been demonstrated to play an important role in the pathogenesis of AML and they have the potential to be used as a source of biomarkers for the early detection of AML, for monitoring measurable residual disease (MRD) and for detecting the appearance of drug resistance. The main aim of this dissertation was to contribute to the identification of possible AML biomarkers present in EVs released by AML cell lines. EVs released by two leukemic cell lines, OCI-AML3 and KG1a, were isolated through differential ultracentrifugation and were characterized in terms of particle morphology, size and concentration by transmission electron microscopy (TEM) and nanoparticle tracking analysis (NTA). Mass spectrometry (MS)-based proteomic analysis was performed and several known EV markers were identified in the EVs released by both cell lines. For instance, heat shock protein HSP 90-beta and α-actinin 4 (accepted EV markers) were detected in EVs shed by the KG1a cell line. The expression of α-actinin 4, CD81 and syntenin-1 (accepted EV markers) in EVs shed by the OCI-AML3 cell line was confirmed by Western Blot. The proteomic analysis also identified some clinically established AML immunophenotypic protein markers (LAIPs) in the isolated EVs, namely CD14 and CD33 in the EVs released by the OCI-AML3 cell line, and CD7 and CD34 in EVs released by the KG1a cell line. The presence of CD14 and CD33 was then confirmed in OCI-AML3-derived EVs, by Western Blot analysis. In addition, proteomic results demonstrated that moesin, α-2-macroglobulin, filamin-a and non-POU domain containing octamer-binding protein were highly abundant in EVs released by the OCI-AML3 cell line and that moesin, α-enolase and cofilin-1 were highly abundant in EVs released by the KG1a cell line. According to the literature, all of these proteins have been previously associated with tumorigenesis and/or drug resistance, thus having potential as candidate biomarkers of AML. Importantly, moesin, α-enolase and filamin-a were simultaneously highly abundant in EVs released by both cell lines, suggesting their potential as MRD AML biomarkers. This hypothesis will need to be confirmed in future studies, extending this analysis to other AML cell lines and to non-tumor cell lines as controls. Further studies are also needed to confirm the preliminary results obtained regarding the proteomic analysis of the KG1a cell line and EVs. Ultimately, this work might contribute to a better understanding of the potential of EVs as sources of biomarkers in AML.